The synthesis of Paris saponin VII mainly occurs in leaves and is promoted by light intensity - Wen, Feiyan; Chen, Siyu; Wang, Yue; Wu, Qinghua; Yan, Jie; Pei, Jin; Zhou, Tao (Frontiers in Plant Science, 2023)
Unravelling the specific organ and tissue involved in saponin synthesis, ae well as the light regulatory mechanisms, is crucial for improving the quality of artificial cultivated medicinal materials of Paris plants. Paris saponin Ⅶ (PS Ⅶ), a high-value active ingredient, is found in almost all organs of Paris plant species. In this study, we focused on PPY and found that PS Ⅶ synthesis predominantly occurs in leaves and is enhanced by high light intensity. This intriguing discovery has unveiled the potential of manipulating non-traditional medicinal organ leaves to improve the quality of medicinal organ rhizomes. The analysis of organ differences on saponins concentration in PPC, PF and PPY revealed consistency among the three Paris species, which was mainly dominated by PS Ⅶ. Notably, the leaves and stems exhibited much higher proportions of PS Ⅶ compared to other organs, accounting for 80-90% of the four main saponins. Among the three Paris species, PPY had the highest concentration of PS Ⅶ and was selected for subsequent experiments. Further investigations on saponin subcellular localization, temporal variation, and stem wound fluid composition demonstrated that PS Ⅶ is synthesized in mesophyll cells, released into the intercellular space through exocytosis, and then transported to the rhizome via vascular tissue. These findings confirm the significant role of leaves in PS Ⅶ synthesis.Additionally, a 13 C-glucose feeding to trace PS Ⅶ biosynthesis revealed that only PS Ⅶ in the leaves exhibited incorporation of the labeled carbon, despite conducting 13 C-glucose feeding in leaves, stems, rhizomes, and roots. Thus, the leaves are indeed the primary organ for PS Ⅶ synthesis in PPY. Furthermore, compared to plants under 100 μmol m −2 s −1 , plant under 400 μmol m −2 s −1 exhibited higher PS Ⅶ concentration, particularly in the upper epidermal cells of the leaves.We propose that high light intensity promotes PS Ⅶ synthesis in leaves through three mechanisms:(1) increased availability of substrates for saponin synthesis, (2) protection of leaves from high light damage through enhanced saponin synthesis, and (3) enhanced the compartmentalization of saponins within the leaves, which in turn feedback regulates saponin synthesis.